Africa Needs to Prioritize one Health Approaches that Focus on the Environment, Animal Health and Human Health - Otu, Akaninyene; Efa, Emmanuel; Meseko, Clement; Cadmus, Simeon; Athingo, Rauna; Namisango, Eve; Ogoina, Dimie; Okonofua, Friday; Ebenso, Bassey (Nature Medicine, 2021)
The past two decades have witnessed a global increase in the frequency of emerging and re-emerging infectious-disease epidemics. African countries have experienced the devastating impact of successive epidemics that are projected to have caused a loss of over 227 million years of healthy life and an annual productivity loss of over US$800 billion across the continent1. Between 2016 and 2018, over 260 infectious-disease epidemics, disasters and other potential public-health emergencies were identified in Africa, with 41 (79%) of the 52 countries in the region recording at least one epidemic during that period2. The five top causes of disease epidemics were cholera, measles, viral hemorrhagic diseases, malaria and meningitis.